Incidence of celiac disease autoimmunity and associations with maternal tuberculosis and pediatric Helicobacter pylori infections in 4-year-old Ethiopian children followed up in an HLA genotyped birth cohort - Adugna Negussie Gudeta; Carin Andrén Aronsson; Bayissa Bekele Binagdie; Alemayehu Girma; Daniel Agardh (Frontiers Media S.A., 2022)
BackgroundThe prevalence of celiac disease in the general population is mainly unknown in most of sub-Saharan African countries. The aim of this study was to determine the incidence of celiac disease autoimmunity (CDA) and its associations with latent Mycobacterium tuberculosis (LMTB) and Helicobacter pylori (HP) infections in Ethiopian children aged 4 years in an HLA genotyped cohort study.MethodsOf 1,389 recruited children between 2018 and 2022, 1,046 (75.3%) had been screened at least twice for celiac disease between the ages of 2 and 4 years using a tissue transglutaminase autoantibody (tTGA) ELISA kit. Tissue TGA-positive children were retested using radio-binding assays. CDA was defined as persistent-confirmed tTGA positivity in two consecutive samples. Associations of CDA with LMTB and HP were tested in a subpopulation of 752 children born to mothers who were previously tested for LMTB with IFN-γ and anti-HP antibodies in samples collected at a mean age of 49.3 ± 5.3 months.ResultsScreening detected 38 out of 1,046 (3.6%) IgA-tTGA-positive children. Ten (1.0%) were confirmed to be positive, with six (0.6%) children diagnosed with CDA. The incidence of CDA at 4 years of age was 1.2 per 1,000 person-years. LMTB was found in 4 of 6 (66.7%) mothers with CDA children compared with 340 of 734 (46.3%) mothers of children without CDA (p = 0.424), while HP was found in 3 of 6 (50.0%) CDA children compared with 315 of 746 (42.2%) children without CDA (p = 0.702).ConclusionThe incidence of CDA in Ethiopian children is lower than the pooled global incidence. Neither LMTB nor HP infections are associated with CD in Ethiopian children.